2013
DOI: 10.1063/1.4818987
|View full text |Cite
|
Sign up to set email alerts
|

Hot electron production and diffuse excited states in C70, C82, and Sc3N@C80 characterized by angular-resolved photoelectron spectroscopy

Abstract: Angular-resolved photoelectron spectroscopy using wavelength-tuneable femtosecond laser pulses is presented for a series of fullerenes, namely, C70, C82, and Sc3N@C80. The photoelectron kinetic energy distributions for the three molecules show typical thermal electron spectra with a superimposed peak structure that is the result of one-photon ionization of diffuse low-angular momenta states with electron density close to the carbon cage and that are related to so-called super atom molecular orbitals. Photoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…A fundamental understanding of the electronic structure and photo-initiated nuclear dynamics in these molecules can be achieved by probing relaxation channels and re-organizational dynamics of highly excited molecules. This will enable understanding of large organic molecules and carbon nanomaterials, important for optimizing their properties for use in molecular electronics and organic photovoltaics (46).…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental understanding of the electronic structure and photo-initiated nuclear dynamics in these molecules can be achieved by probing relaxation channels and re-organizational dynamics of highly excited molecules. This will enable understanding of large organic molecules and carbon nanomaterials, important for optimizing their properties for use in molecular electronics and organic photovoltaics (46).…”
Section: Introductionmentioning
confidence: 99%
“…The main difference in the photoelectron spectra is a broadening of the peak widths and a more prominent double-peak structure for the p-SAMO band due to the decreasing symmetry as the size of the fullerene cage is increased. The peak structure for the first s-and p-SAMO bands is almost completely smeared out for the endohedral fullerene, Sc 3 N@C 80 [9].…”
Section: Fullerene Super-atom Molecular Orbitals and Rydberg Statesmentioning
confidence: 86%
“…The details of the experimental techniques have been provided in previous publications [5,8,9] and will be only briefly described here. The original studies that reported the excitation and subsequent single-photon ionization of Rydberg states in C 60 were carried out with a combined linear time-of-flight photoelectron spectrometer and a time-of-flight mass spectrometer (MS) [5,10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations